2016
DOI: 10.1007/s12282-016-0703-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Japanese version of the BREAST-Q and the traditional psychometric test of the mastectomy module for the assessment of HRQOL and patient satisfaction following breast surgery

Abstract: Background: The objective of the study was to compare direct measurement with a conventional method for evaluation of clip placement in stereotactic vacuum-assisted breast biopsy (ST-VAB) and to evaluate the accuracy of clip placement using the direct method. Methods: Accuracy of clip placement was assessed by measuring the distance from a residual calcification of a targeted calcification cluster to a clip on a mammogram after ST-VAB. Distances in the craniocaudal (CC) and mediolateral oblique (MLO) views wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Research by other authors later showed similar results [ 29 , 30 ]. In addition, similar findings are found in other papers, namely, women in all ages after radical mastectomy had the worst level of general satisfaction with life [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…Research by other authors later showed similar results [ 29 , 30 ]. In addition, similar findings are found in other papers, namely, women in all ages after radical mastectomy had the worst level of general satisfaction with life [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 88%
“…These findings again could relate to the fact that the original sample is more heterogeneous, as participants were included from a range of weight loss and plastic surgery healthcare providers from 4 countries (England, Scotland, the United States, and Canada). Saiga et al 33 , 34 recently published a Japanese translation and psychometric analysis of the BREAST-Q and also found ceiling effect in the experience of care scales. They suggest that the ceiling effect could be associated with study design, which could also be the situation in our design, where patients were asked to fill out the BODY-Q as preparation for their follow-up visit in the outpatient clinic.…”
Section: Discussionmentioning
confidence: 99%
“…The following subscales are used in this study: satisfaction with breasts, satisfaction with implant, psychosocial well-being, sexual well-being, adverse effects of radiation, physical well-being of chest and upper extremity, satisfaction with abdomen, physical well-being of abdomen, satisfaction with back appearance, and physical well-being of shoulder and back. A formal Japanese version was developed, 45 and the validation of the reconstruction module has been completed (Cronbach α>0.7, inter-rater reliability (intraclass correlation coefficient (ICC)>0.8).…”
Section: Breast-qmentioning
confidence: 99%
“…Some patients might feel psychological distress when asked about their sexual well-being. 45 The estimated time to complete a survey is about 10 min, and this may be a burden.…”
Section: Harmsmentioning
confidence: 99%